Media authoring and othering on Islam and muslims in Malaysian chinese newspapers : a case study on Sin Chew Daily and Oriental Daily - Wong, Siew Ying (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This work studies the media authoring and Othering on Islam and Muslims in Malaysian Chinese newspapers, the Sin Chew Daily and Oriental Daily, beginning from 1st Jan 2011 to 30th April 2011. Specifically, this work attemps to discover how news narratives on Islam and Muslims are being authored, to explore the narratives of preferred authoring on Othering, to extract practices of authoring, and to understand the Chinese newspapers logic of authoring with regard to the Other. Qualitative methodology is being employed as the framework of study with the theories of Boundaries and Othering narratives as its underpinning theories. Data analysis revolves around four types of Othering naratives, as adopted and adapted from Kamppi (2008), with hermenneutics being used as a device of knowing. The four types of Othering were the narative of violence, the colonialist narrative, the narrative of secularism and the narrative of clash of culture. The study found that the grand narrative of both newspapers were on the distorted imagination about the Iislamic state and Iislamic law of Hudud. It suffices to say the authoring on Islam and Muslims in these two newspapers is a 'played' work with a purpose, perhaps to created anxieties or moral panic within the border for the political and social advantes of a certain gropu within the readers' larger community. Knowingly or unknowingly, both newspapers were and are boundary-makers. In this regard readers were kept 'captive' by the specified authored knowledge on Islam and Muslims within the border. Simply, authoring in both newspapers were preferred authoring with preferred meaning, which promotes or suggest a constructed logic-interest of presentation.